CARBON-COMPOSITE MATERIAL WITH IMPROVED MISCIBILITY AND METHOD AND APPARATUS FOR CONTINUOUSLY PRODUCING THE SAME - JEON SEONG YUN; HONG SONGOL; OH JOO SEOK; HAN JOO HEE; LEE JIN SEO; DO SEUNG HOE; JUNG MAN WOO (2014)
PROBLEM TO BE SOLVED: To provide a method for producing carbon nanotube composite material which shows excellent dispersibility and improved conductivity in a matrix even with a small added amount.SOLUTION: The method for producing carbon nanotube composite material comprises the steps of: a) introducing a mixture including carbon nanotubes, at least one carbon compound other than the carbon nanotubes and a dispersion medium into a preheating unit under a pressure of 1 to 400 atm to preheat the mixture; b) treating the preheated mixture under a sub-critical or super-critical condition of 50 to 400 atm; c) cooling and depressurizing the resultant product in the b) step to 0 to 100°C and 1 to 10 atm; d) and recovering the cooled and depressurized product. 【課題】少量の添加で基材内において分散性に優れ伝導性が向上した炭素ナノチューブ複合素材の製造方法を提供する。【解決手段】ａ）炭素ナノチューブ、炭素ナノチューブ以外の１種以上の炭素化合物及び分散媒を含む混合物を１乃至４００ａｔｍの圧力で予熱槽に注入して予熱する段階と、ｂ）前記予熱された混合物を５０乃至４００ａｔｍの亜臨界または超臨界条件において処理する段階と、ｃ）前記ｂ）段階の生成物を０乃至１００℃に冷却及び１乃至１０ａｔｍに減圧する段階と、ｄ）前記冷却／減圧された生成物を回収する段階と、を含む炭素ナノチューブ複合素材の製造方法。【選択図】図１